Familial Paraphilia: A Pilot Study with the Construction of Genograms. (4th March 2012) - Labelle, Alain; Bourget, Dominique; Bradford, John M. W.; Alda, Martin; Tessier, Pierre
Abstract : Biological factors are likely predisposing and modulating elements in sexually deviant behavior. The observation that paraphilic behavior tends to cluster in some families is intriguing and potentially raises questions as to whether shared genetic factors may play a role in the transmission of paraphilia. This pilot study introduces five families in which we found presence of paraphilia over generations. We constructed genograms on the basis of a standardized family history. Results document the aggregation of sexual deviations within the sample of families and support a clinical/phenomenological heterogeneity of sexual deviation. The concept of paraphilia in relation to phenotypic expressions and the likelihood of a spectrum of related disorders must be clarified before conclusions can be reached as to family aggregation of paraphilia based on biological factors.